2017
DOI: 10.1016/j.clim.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen decreases tight junction protein ZO-1 expression in human primary gut tissues

Abstract: Females have a higher prevalence of most autoimmune diseases; however, the mechanism is unknown. In this study, we examined the expression of tight junction protein zonula occludens 1 (ZO-1) and estrogen receptor (ER)-α/β in human primary gut tissues by immunohistochemistry, immunofluorescence and qPCR. The expression of ZO-1 and ER-β but not ER-α was present in both male and female gut tissues. There was no sex difference in ER-β expression, but ZO-1 expression was decreased in females compared to males. In v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 62 publications
(59 reference statements)
1
30
0
Order By: Relevance
“…The statistical analysis for the immunofluorescence of ZO-1 was performed by ImageJ (Bethesda, USA). 28,29 Briefly, the image was opened with the ImageJ software. It was reversed to gray scale and the optical density was calibrated.…”
Section: Immunofluorescencementioning
confidence: 99%
“…The statistical analysis for the immunofluorescence of ZO-1 was performed by ImageJ (Bethesda, USA). 28,29 Briefly, the image was opened with the ImageJ software. It was reversed to gray scale and the optical density was calibrated.…”
Section: Immunofluorescencementioning
confidence: 99%
“…For example, during pregnancy, certain plasma estrogens increase up to 1000-fold, with a return to near prepregnancy levels generally within the first few hours postpartum (Russell et al, 2001). Importantly, studies from others and ours have also suggested that estradiol and human choionic gonadotophin (hCG) may have the ability to increase the mucosal permeability (Herr et al, 2013; Kuruca et al, 2017; Zhou et al, 2017). Consequently, the alteration of sex hormones in pregnant women with depression may result in a disruption of mucosal barriers, and subsequently ignite an elevated microbial translocation and systemic Inflammation.…”
Section: Discussionmentioning
confidence: 88%
“…Similar protective effects of estrogen have been observed in the vaginal epithelium [100] . In contrast, a recent study showed that estrogen decreases tight junction protein zonula occludens 1 (ZO-1) expression in primary colonic tissues isolated from post-menopausal women and men [101] . Consistent with this finding, the effect of hormone supplementation in metabolic health of post-menopausal women contrasts to those observed in pre-menopausal women, suggesting that the loss of ovarian function due to menopause may have profound and differential impact on estrogen signaling compared to pre-menopausal women [102] , [103] , [104] .…”
Section: Gastrointestinal Tract and Sexual Dimorphismmentioning
confidence: 89%